Plant of interest — Prunella vulgaris L. - Sárosi, Sz.; Bernáth, J. (International Journal of Horticultural Science, 2007)
Self-heal (Prunella vulgaris L.), known as a remedy traditionally used as Chinese medicine, was neglected in modern pharmacy until the 20th century. Although in the Middle Ages it was respected for its wound-healing effect, the usage of this medicinal plant was confined just to the conventional pharmacy. Nowadays, because of the great dislike of synthetic materials, however, self-heal has become one of the most important target plants again. Owing to its valuable active constituents, besides its wound-healing effect, the plant can also be used as hepato-protective, antioxidant, anti-HIV, anti-cancer remedy, and it is effective against Herpes virus, as well. Its taste — and odourless extracts are applied by the food industry as natural food preservatives. Taking into account the importance of self-heal our aim was to introduce this plant species more detailed with regard to its active agents, effects and cultivation methods.